Diversity of fenoforms in Aesculus hippocastanum L. - O.K. Doroshenko (Інтродукція Рослин, 2009)
As a result of fenological observation of early, late and intermediate fenoforms of Aesculus hippocastanum L. 6 fenoforms were found. Thanks to obtained result author recommends to grow nurse-woods of this forms for reproduction and use in the ornamental plantations.